Lysosomal tracking with a cationic naphthalimide using multiphoton fluorescence lifetime imaging microscopy. Issue 81 (22nd September 2017) - Li, Meng; Ge, Haobo; Mirabello, Vincenzo; Arrowsmith, Rory L.; Kociok-Köhn, Gabriele; Botchway, Stanley W.; Zhu, Weihong; Pascu, Sofia I.; James, Tony D.
Abstract : A naphthalimide-based chemosensing motif capable of turning on the fluorescence emission in solution and in vitro is reported. Abstract : A naphthalimide-based chemosensing motif turns ON the fluorescence emission in solution in the presence of aqueous iron(iii ) chloride, and maintains this property in living cancer cells. The emission response to Fe(iii ) ions occurs simultaneously with a change in pH. The protonation of methyl piperazine-conjugated naphthalimide promotes its lysosomal localisation as assessed by co-localisation tests and fluorescence lifetime imaging microscopy (FLIM) in vitro.